Mefloquine compared with doxycycline for the prophylaxis of malaria in Indonesian soldiers. A randomized, double-blind, placebo-controlled trial. - Ohrt C; Richie TL; Widjaja H; Shanks GD; Fitriadi J; Fryauff DJ; Handschin J; Tang D; Sandjaja B; Tjitra E; Hadiarso L; Watt G; et al. (Annals of internal medicine, 1997)
BACKGROUND: Mefloquine and doxycycline are the two drugs recommended for prophylaxis of malaria for visitors to areas where Plasmodium falciparum is resistant to chloroquine. OBJECTIVE: To compare the efficacy and tolerability of mefloquine with those of doxycycline as prophylaxis for malaria. DESIGN: Randomized, double-blind, placebo-controlled field trial of chemoprophylaxis of malaria. SETTING: Northeastern Irian Jaya, Indonesia. PARTICIPANTS: 204 Indonesian soldiers. INTERVENTION: After radical curative treatment, participants were randomly assigned to receive 100 mg of doxycycline per day and mefloquine placebo; 250 mg of mefloquine per week (preceded by a loading dose of 250 mg/d for 3 days) and doxycycline placebo; or placebos for both drugs. Prophylaxis lasted approximately 13 weeks. MEASUREMENTS: The primary end point for efficacy was the first occurrence of malaria, as documented by a positive malaria smear. Malaria smears were obtained weekly and when patients had symptoms suggesting malaria. Reported symptoms were recorded daily, and an exit study questionnaire was conducted. RESULTS: In the placebo group, 53 of 69 soldiers developed malaria (9.1 person-years), resulting in an attack rate of 5.8 cases per person-year (95% CI, 4.3 to 7.7 cases per person-year). Plasmodium falciparum accounted for 57% of cases, and P. vivax accounted for 43% of cases. No malaria occurred in the 68 soldiers (16.9 person-years) in the mefloquine group; thus, the protective efficacy of mefloquine was 100% (CI, 96% to 100%). In the doxycycline group, P. falciparum malaria occurred in 1 of 67 soldiers (16.0 person-years), yielding a protective efficacy of 99% (CI, 94% to 100%). Both drugs were very well tolerated. CONCLUSIONS: Mefloquine and doxycycline were both highly efficacious and well tolerated as prophylaxis of malaria in Indonesian soldiers.